TRADITIONAL ECOLOGICAL KNOWLEDGE OF THE KAZAKH PEOPLE AS A PREREQUISITE FOR EDUCATION FOR SUSTAINABLE DEVELOPMENT - Shakirova, Nurzhanat; Kaimuldinova, Kulyash; Shakirova, Araily; Wendt, Jan A. (Pedagogy and Psychology, 2023)
Nowadays, environmental education is being transformed into education for sustainable development (ESD). The concept of sustainable development is a necessary condition for the continuation of life on Earth. The knowledge of the environment of Kazakh people includes a deep knowledge of the state of the climate, the spatial laws of climatic processes, and atmospheric phenomena. From the point of view of ethnic Genesis, the concept of space of people is reflected in the spiritual culture, and their traditional worldview is the basis of public consciousness. The developed spatial understanding of the Kazakh world can be traced both through its economic organization and through the toponymic system of space. The purpose of this article is to analyze and demonstrate deep knowledge of the Kazakh people about climatic conditions as a result of their adaptation to harsh environmental conditions. Of particular interest is knowledge in the field of forecasting weather conditions, which is an indicator of the traditional knowledge of residents who have long had a nomadic lifestyle. As the experience of classical nomads shows, very important environmental knowledge was required to adequately organize nomadic herding. To adapt to these environmental conditions, a very large minimum amount of information was required, and the quality and volume of knowledge could only be subjected to transmission and accumulation from generation to generation over a very long period of history. Quantitative data were analyzed and interpreted using descriptive statistics. The literature review was conducted based on the recommendations of the PRISMA methodology.A lot of literature is written about the importance of the environmental experiences of our people. Therefore, in the context of globalization, it is important to awaken the national consciousness to stop the actions that lead to environmental destruction and climate change, that is, to use the experiences of the ancestors of each nation to preserve the habitat. The purpose of this article is to analyze and demonstrate deep knowledge of the Kazakh people about climatic conditions as a result of their adaptation to harsh environmental conditions. Of particular interest is knowledge in the field of forecasting weather conditions, which is an indicator of the traditional knowledge of local residents who have long had a nomadic lifestyle. The pedagogical and psychological basis of the Kazakh worldview on climatic processes is very high. Therefore, when teaching climate change, it is necessary to take into account local population factors. The Kazakh people especially cherish their native land. As the experience of classical nomads shows, very important environmental knowledge was required to adequately organize nomadic herding. To adapt to these environmental conditions, a very large minimum amount of information was required, and the quality and volume of knowledge could only be subjected to transmission and accumulation from generation to generation over a very long period of history. A lot of literature is written about the importance of environmental experiences of our people. Therefore, in the context of globalization, it is important to awaken the national consciousness in order to stop the actions that lead to environmental destruction and climate change, that is, to use the experiences of the ancestors of each nation to preserve the habitat.